Interoperability of fast charging station with battery booster - Schindler, Josef; Watson, Venesa; Waedt, Karl (Lecture Notes in Informatics (LNI), Proceedings - Series of the Gesellschaft fur Informatik (GI), 2019)
Before a high proportion of Electric Vehicles (EV) will be deployed, sufficient charging infrastructure for these EVs must be provided. In Germany, this deployment is hindered by the lack of a universal standard for the geometry of the charging plugs, the different charging voltage levels, the structure of data that is provided by the charging station and so forth. Related standards such as ISO/IEC 15118 and ISO/IEC 61850, respectively addresses front-end communication between EVs and common charging stations and defines communication messages for grid automation. Whilst ISO/IEC 15118 does address interoperability between charging infrastructures from different manufacturers, its restriction to front-end communication limits the extent of advanced interoperability. In this paper, we investigate the interoperability on battery boosted charging stations based on OPC Unified Architecture (OPC UA). OPC UA, powered by the OPC Foundation, is the primary interoperability standard for Industry 4.0 (I4.0). OPC UA enables data exchange regardless of the manufacturer of individual components. OPC UA can be implemented in embedded devices and controllers without considering additional "black boxes", "windows boxes" or gateways in front of the equipment. This level of interoperability provides significant costsaving for the utilities during all lifecycle phases. It also ensures transparent data acquisition for customers. In this paper, an example of fast charging station with battery booster is used to demonstrate the interoperability feature of OPC UA compared to that of ISO/IEC 15118. Also, their differing structure makes it necessary to consider these charging stations separately from common ones. Therefore, various data representation formats are utilized to show information sharing within two model user groups.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Address space; Fast charging station; Interoperability; Opc ua